Elogio da distância. Apontamentos para o projecto da minha casa - João Gonçalves Neves Castro Paupério (2016)
This master's dissertation has its origins in the possibility of designing a studio-house for oneself. Assuming that architecture remains the art of organizing life within space, the purpose of this thesis will focus on thinking about the design process itself: design that will not exactly stand for a fnished product, but rather for open process, grounding itself on thinking -memory and imagination-, a journey of investigation through which one will learn, recall and synthesise the materials one uses to transform the circumstance which (in)forms it. Willing to (de)focus the artistic relevance of architecture and the house beyond its objectual condition, shifting it into the connection and dialogue it will be able to establish with the variables of concrete reality, one found support in the image-idea of distance (detachment) presented by Luz Valderrama: design as building a detachment space located between the object and the subject to be dwelled by artefacts, gestures, speeches, actions, energies and movements which acumulate time, fnally producing exteriority and space. Therefore, one has organized this investigation in three major moments (distinct but inextricably linked) aiming to insinuate, beyond the project of a studio-house acting as pretext, one's own architectural-project: (1) an approach to the understanding of the dynamic which provokes and guides the inventivness of the design process; (2) the gathering of a series of case studies houses, design triggers which -due to the transversality of the values they share in the relationship they establish with time, with the world, with artefacts, which is to say, with life- have revealed themselves essential to draw/ground the guiding principles for our house; (3) building the distance of one's house from a text and a map of thinking images which simultaneously inhabit and illustrate the current state of the project, in a moment which, unavoidably, precedes the settlement of the drawing (and) of the building itself.